TINJAUAN ATAS IMPLEMENTASI SIKLUS PEMBELIAN DAN PEMBAYARAN BARANG IMPORT STUDI KASUS PT. FANUC - Desy Amaliati Setiawan (Jurnal Inovasi Penelitian, 2022)
This research was conducted at PT. Fanuc A phenomenon that occurs is sometimes an error occurs in the data input purchase and payment of goods, so it must propose improvements to the input data. The formulation of this research is to investigate the implementation of the buying cycle and payment for goods for commercial transactions as well as recording. The method used in this research is descriptive analysis method, data collection techniques done of literature study, field study consisted of interviews, observation and documentation. The results showed that in implementing the buying cycle and payment of goods have been properly and in accordance with the theory that there is visible from the application of the cycle automatically computerized, recording is also done after the goods have been received from the supplier. But sometimes an error occurs in the data input purchase and payment of goods.